Cryogenic thermoacoustics in the SPIRAL2 LINAC. (June 2022) - Ghribi, Adnan; Aburas, Muhammad; Alhaffar, Abdallah; Bernaudin, Pierre-Emmanuel; Duthil, Patxi; Nemer, Maroun; Thermeau, Jean-Pierre
Highlights: Investigation of thermo-acoustic oscillation in heavy ions superconducting linear accelerator. Statistical study of amplitudes and frequencies of TAO. Comparison of different TAO damping solutions. Investigation of damping solutions side effects on cryogenic operation. Abstract: SPIRAL2 is a superconducting LINAC subject to cryogenic thermoacoustic oscillations occurring in its valves boxes. 4 years of monitoring and experimental investigations with thousands of datasets turned these unwanted effects into an opportunity to study and understand thermoacoustics in a complex environment such as a real life accelerator. Without digging deep into Rott's thermoacoustics theory, thoroughly shown in other works, this paper describes the instrumentation and the methods that prepare more advanced modeling of these phenomena either to damp or to harness the energy of cryogenic thermoacoustics.